ENHANCING MENTAL HEALTH LITERACY THROUGH SOCIALIZATION AMONG STUDENTS OF BAITUL ARQAM MUHAMMADIYAH ISLAMIC BOARDING SCHOOL, SIBREH" - Zainab, Syarifah; Alfarizy, Rizky; Rahma, Lisa; Khotimah, Khoirul Rizki; Vatarisa, Desika (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2025)
Mental health is a crucial aspect in developing individuals who are emotionally, psychologically, and socially healthy, especially during adolescence, a vulnerable period for mental disorders. Pesantren, as boarding-based educational institutions, face high stress levels, compounded by low mental health literacy and social stigma that hinder help-seeking behavior. Based on initial screening at Pesantren Baitul Arqam Sibreh, most santri showed limited understanding of mental health and emotional management skills. This community service was conducted through an educational workshop using a participatory learning approach for 32 santri. Activities included a pre-test, interactive material delivery, educational games, and a post-test. Evaluation results indicated improved understanding and positive attitudes toward mental health, with 85% of participants showing significant change. This activity effectively increased mental health literacy and encouraged openness and help-seeking. In conclusion, the socialization plays an important role in creating a more supportive pesantren environment and serves as a foundation for further programs promoting and preventing mental health issues among santri. Keywords: mental health, mental health literacy, santri, pesantren, mental health promotion